Implementation of the Control Function for Employees of the Education and Culture Office of Muara Enim Regency - Eka Susanti; Hardiyansyah Hardiyansyah; Yusnawati Yusnawati (Penerbit Jurnal Indonesia, 2023)
This research was conducted at the Department of Education and Culture, Mùara Èním Regency. The aim of the study was to analyze how the Implementation of the Control Function in the Employees of the Department of Education and Culture in the Regency of Mùara Èním. Sources of data in this study are primary data and secondary data. There are two methods of data collection in this study, namely literature study and field study consisting of observation, interviews and documentation. The controls in the Education and Culture Office of Mùara Èním Regency have generally been well implemented, such as: 1). Control over the activities that will be carried out by employees. The process of controlling activities or work programs has been carried out by determining who will carry out these activities and how these activities are carried out and where these activities are carried out. 2). Control over the process of determining the boundaries of what employees will do by determining the expected results. In this control, employees know what limits can be done with the aim of getting results as expected. 3). Control in determining the direction so that all activities run according to the target. In this control, employees in carrying out their activities have directions and goals or objectives that have been determined by the leadership. 4). Control in determining the organizational structure and division of tasks for each employee. Employees are given tasks according to their main duties and functions.